Variation in physical and mechanical properties of fired-clay bricks incorporating ETP biosolids. (15th April 2016) - Ukwatta, Aruna; Mohajerani, Abbas; Eshtiaghi, Nicky; Setunge, Sujeeva
Abstract: This study was directed towards investigating the possibility of incorporating biosolids from Melbourne's Eastern Treatment Plant (ETP) in fired clay bricks. First, the mineralogical and chemical compositions as well as geotechnical characteristics of the ETP biosolids and brick soil were determined. Then, bricks were fabricated with five different percentages of ETP biosolids (5%, 15%, 25%, 35%, and 50%) by firing them at a temperature 1020 °C for 3 h. The effect of incorporating ETP biosolids in a ceramic body on the physical and mechanical properties of fired-bricks was assessed by shrinkage, weight loss on ignition (LOI), water absorption, density, initial rate of absorption (IRA), compressive strength, efflorescence, scanning electron microscopy (SEM), and leachate analysis. The compressive strength of biosolids amended bricks ranged from 24.9 to 37.0 MPa, which met the requirements of the Australian Standards. Moreover, bricks with ETP biosolids can save up to 25% of energy during the firing in an electric furnace, which is very important in terms of sustainable development. The leachate analysis results showed that the concentration of heavy metals leached is insignificant and much lower than the regulatory limits. Highlights: Biosolids were used as a partial replacement of raw material in fired-clay bricks (FCB). Biosolids amended bricks (BFCB) showed satisfactory physical and mechanical properties. Addition of biosolids to FCB can contribute significantly to the required firing energy. Leachates of heavy metals from BFCB were much lower than regulatory limits. Biosolids can be regarded as a promising raw material in manufacturing bricks.